Combining Parameters of Fuel and Greenhouse Gas Costs as Single Objective Function for Optimization of Power Flow - Ignatius Riyadi Mardiyanto; Hermagasantos Zein; Adi Soeprijanto (Universitas Ahmad Dahlan, 2017)
The Kyoto Protocol is a protocol that highlights on greenhouse gases that have been adopted by many countries. Based on this protocol, power plants that produce emissions are encouraged to pay compensation. Conventionally, optimization of fuel mix in the electric power system components has not involved emission charges on the electricity system. This paper proposes a single objective function of amathematical model for the calculation of power flow optimization involving greenhouse gas emissions costs to the fuel cost function. The single objective function derived using the mathematical model approach with linear heat rate function, in order to get the relationship between the fuel cost function with GHG emission. Namely, the function of energy costs as a combination of fuel costs and GHG emission costs can be shown as a quadratic function.